Rice endophytes and their potential applications - Hemanth Kumar, Jayabalakrishnan; Vigneshwaran, Muralidharan; Vignesh, Annamalai; Babu, Subramanian (Journal of Scientific Agriculture, 2020)
Endophytic microbial communities in crop plants are beginning to be explored. These microbes are either carried through seeds or establish colonization in the plants from soil based on chemotaxis of root exudates. Variability and diversity of endophytic bacteria and fungi have been observed in rice plants in different plant parts and growth stages. Genotypic variations are observed between Indica and Japonica. Pseudomonas, Bacillus, Streptomyces, Azospirillum, Azotobacter are some of the dominating genera of bacteria in internal tissues of rice plants. These endophytes provide benefits such as tolerance to abiotic stresses, defense against pest and diseases, nutrient solubilization and mobility. In addition, many metabolites are characterized from the endophytes that are useful in other branches of biotechnology including bioremediation. Complete characterization of microbiome of rice plants under various soil agro-climatic zones and understanding their population dynamics, co-occurrence and networking will help in identifying useful strains for developing new biofertilizers, plant growth promoting microbes and biopesticides.